Personalised nutrition and health. (13th June 2018) - Ordovas, Jose M; Ferguson, Lynnette R; Tai, E Shyong; Mathers, John C
Abstract : Jose Ordovas and colleagues consider that nutrition interventions tailored to individual characteristics and behaviours have promise but more work is needed before they can deliver